Treatment of walled-off necrosis using lumen-apposing metal stents versus plastic stents: a systematic review and meta-analysis of data from randomized trials - Bang, Ji Young; Wilcox, Charles Melbern; Navaneethan, Udayakumar; Hawes, Robert Holbrook; Varadarajulu, Shyam (Endoscopy, 2023)
Background Walled-off necrosis (WON) is highly morbid disease most effectively managed by endoscopic drainage with lumen-apposing metal stents (LAMSs) or plastic stents, with or without necrosectomy. This meta-analysis compared the clinical outcomes of patients included in randomized trials treated using LAMSs or plastic stents.Methods The MEDLINE and EMBASE databases were searched to identify all data collected from randomized trials comparing LAMSs and plastic stents for the treatment of WON. The primary outcome measure was need for endoscopic necrosectomy.Results Three studies comprising 206 patients met inclusion criteria. Except for procedure duration, which was significantly shorter for LAMSs (standardized mean difference [SMD] −1.22, 95%CI −1.64 to −0.79), there was no significant difference in need for necrosectomy (38.5% vs. 41.2%; risk ratio [RR] 1.07, 95%CI 0.79–1.45), number of interventions (SMD −0.09, 95%CI −0.40 to 0.22), treatment success (90.7% vs. 94.5%; RR 0.96, 95%CI 0.87–1.06), recurrence (4.6% vs. 0.6%; RR 3.73, 95%CI 0.42–33.0), readmission (42.6% vs. 50.2%; RR 0.84, 95%CI 0.62–1.14), length of hospitalization (SMD −0.06, 95%CI −0.55 to 0.43), mortality (8.5% vs. 9.8%; RR 0.70, 95%CI 0.30–1.66), new-onset organ failure (10.6% vs. 14.6%; RR 0.72, 95%CI 0.16–3.32), bleeding (11.0% vs. 10.7%; RR 1.09, 95%CI 0.34–3.44), procedural adverse events (23.6% vs. 19.2%; RR 1.38, 95%CI 0.82–2.33), or overall costs (SMD −0.04, 95%CI −0.31 to 0.24) between LAMSs and plastic stents, respectively. Conclusions Except for procedure duration, there is no significant difference in clinical outcomes for patients with WON treated using LAMSs or plastic stents.